Numerical analysis of 3D dynamic problems of the Cosserat elasticity theory subject to boundary symmetry conditions - Sadovskaya, O. V. (Computational mathematics and mathematical physics, 2009)
In the framework of the Cosserat continuum model, one-dimensional solutions describing plane longitudinal waves, transverse (shear) waves with particle rotation, and torsional waves are analyzed. Boundary symmetry conditions for various types of loading are found. A parallel computational algorithm is worked out for solving 3D dynamic problems of the Cosserat elasticity theory on multiprocessor computer systems. Computations of the propagation of the stress and strain waves induced by a point impulse force in an elastic medium are performed.